Toward Sustainable Food Crop Agriculture In Rural Area By Employing Social Entrepreneur And Penta Helix Approaches: Systematic Literature Review - Sukarli, Sukarli; Syahni, Rahmat; Elfindri, Elfindri; Tanjung, Hery Bachrizal (Riviera Publishing, 2026)
Ideally, tropical countries have great potential in agricultural resources, but the fact is that the agricultural world in most tropical countries, especially in rural areas, is often hampered in development due to many factors, including an understanding of various problems and governance systems that still do not work optimally. Basically, sustainable agriculture (SA) can be realized optimally if the dimensions, especially socio-economic-environment, are able to run synergistically. Socio-economic functions supported by a conducive environment are key in efforts to realize SA. In this study, we have conducted a Systematic Literature Review which aims to analyze various problems in an effort to improve SA performance based on the synergy of these dimensions, especially for the case of food crop agriculture. We emphasize attention to the phenomenon of social entrepreneurship (SE) which of course demands the synergy of existing key dimensions. In addition, we also conducted a literature review that discusses the phenomenon of multi-helix implementation to improve the performance of a managerial system involving multi-stakeholders. We find that the literature describing multi-helix models (e.g. penta-helix) to support the performance of SA systems is still very rare. Even throughout the search that we have done, there have been no reports that specifically discuss the penta-helix (PH) model, especially in the case of food crop agriculture. The results of this study are expected to be a guide for academics and all interested parties in understanding the SE phenomenon more deeply and the potential for PH implementation, especially for the case of food crop agriculture.